Advanced Low-Dimensional Carbon Nanomaterials for Oxygen Electrocatalysis - Yue Yan; Ying Xin; Qingshan Zhao (Nanomaterials)
Amid rising global energy demand and worsening environmental pollution, there is an urgent need for efficient energy storage and conversion technologies. Oxygen electrocatalytic reactions, specifically the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) are critical processes in these technologies. Low-dimensional carbon nanomaterials, including zero-dimensional carbon dots, one-dimensional carbon nanotubes, and two-dimensional graphene, demonstrate substantial potential in electrocatalysis due to their unique physical and chemical properties. On the one hand, these low-dimensional carbon materials feature distinct geometric structures that enable the customization of highly active sites for oxygen electrocatalysis. On the other hand, the sp2 hybridization present in these materials contributes to the existence of π electrons, which enhances conductivity and facilitates catalytic activity and stability. This article reviews recent advancements in the development of efficient catalysts for oxygen electrocatalysis based on low-dimensional carbon nanomaterials, focusing on their characteristics, synthesis methods, electrocatalytic performance, and applications in energy conversion devices. Additionally, we address the current challenges faced by these nanomaterials and outline future research directions to expedite their practical applications.